2014
DOI: 10.1007/s40620-014-0144-2
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a disease management program focused on acquisition of self-management skills in pre-dialysis patients with diabetic nephropathy: 24 months follow-up

Abstract: A well-designed disease management program might be useful for maintaining renal function and improving HbA1c in patients with diabetic nephropathy. It is considered that modification of patient behavior contributed to these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 16 publications
2
34
1
2
Order By: Relevance
“…Based on the finding, the difference of physical health status was not significant before and after self-management counseling in the intervention and the control group. This is in accordance with a previous study by Kazawa, Takeshita, Yorioka, and Moriyama (2015) which reported that disease management programs during 12 months are unable to improve the health status of diabetic nephropathy patients. However, there were several previous studies showing different results.…”
Section: Discussionsupporting
confidence: 93%
“…Based on the finding, the difference of physical health status was not significant before and after self-management counseling in the intervention and the control group. This is in accordance with a previous study by Kazawa, Takeshita, Yorioka, and Moriyama (2015) which reported that disease management programs during 12 months are unable to improve the health status of diabetic nephropathy patients. However, there were several previous studies showing different results.…”
Section: Discussionsupporting
confidence: 93%
“…Evidence concerning the beneficial effects of greater empowerment through education programs is inconclusive. While a Cochrane systematic review studying the effects of education programs in diabetes and CKD concluded that the evidence was poor [ 25 ], more recent studies have reported that education programs improve self-management, glycaemic control, and prevent kidney function decline [ 26 , 27 ]. Nevertheless, given studies showing the importance of patient empowerment and self-management in diabetes [ 28 , 29 ] or in CKD [ 30 , 31 ] and the emphasis that patients and their carers placed on the patient self-management and empowerment in our study, both factors should be considered central in a person-centred health system for co-morbid diabetes and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the multidisciplinary management of DKD were conducted in different sociocultural environments. They reported diverse sex percentage and an age range of 44-74.6% [25][26][27][28][29]. One report showed >50% higher diabetes prevalence in men [30,31].…”
Section: Discussionmentioning
confidence: 99%